2016
DOI: 10.5851/kosfa.2016.36.6.807
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Addition of Encapsulated Collagen Hydrolysate on Some Quality Characteristics of Sucuk

Abstract: The effect of addition commercial fish collagen hydrolysate and encapsulated fish collagen hydrolysate on the quality characteristics of sucuk (a traditional Turkish dry-fermented sausage) was investigated. Fish collagen hydrolysates were encapsulated with maltodextrin (MD) which has two different dextrose equivalent (12DE and 19 DE), with two different types of core/coating material ratios (10% peptide : 90% MD, 20% peptide : 80% MD). Than six group of sucuk dough (control, peptide, MD1210, MD1220, MD1910, MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Table 2 showed the highest moisture content found in the control group and BHT added group, the lowest group is the P3 samples significantly different (P< 0.05) from the control group. Palamutoǧlu and Sariçoban [16] suggested that the effect of collagen hydrolyzate addition to the sucuk samples lowers the moisture content. There was no significant (P >0.05) difference found between water activity of control and hydrolyzate added groups and also there was no significant difference found between pH values of all samples.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 showed the highest moisture content found in the control group and BHT added group, the lowest group is the P3 samples significantly different (P< 0.05) from the control group. Palamutoǧlu and Sariçoban [16] suggested that the effect of collagen hydrolyzate addition to the sucuk samples lowers the moisture content. There was no significant (P >0.05) difference found between water activity of control and hydrolyzate added groups and also there was no significant difference found between pH values of all samples.…”
Section: Resultsmentioning
confidence: 99%
“…Soyer et al (2005) found the fat and protein contents were ranged 13.54-32.57% and 10.55-18.52% for the 10, 20 and 30% formulations, respectively. Palamutoglu and Saricoban (2016) The water activity of the sucuk samples was found as 0.950 by (Coşkuner et al, 2010). In this study, moisture and a w of sucuk samples were lower than above mentioned researches.…”
Section: Proximate Analysesmentioning
confidence: 44%
“…Bahasa Indonesia (PUEBI) yang mencakup empat aspek, yaitu 1 Pemakaian tanda baca (penerapan kelima belas tanda baca dalam penulisan dengan kaidahnya masing-masing). (4) Penulisan unsur serapan (cara penulisan unsur serapan, terutama kosakata yang berasal dari bahasa asing) ( Kemdikbud, 2016).…”
Section: Ejaan Bahasa Indonesia Saat Ini Mengacu Kepada Pedoman Umum unclassified